PERAN HUMAS PEMERINTAH KOTA DENPASAR MENUJU DENPASAR SMART CITY - Sumerta Putri, Ni Made Ambarani; Pascarani, Ni Nyoman Dewi; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2017)
Nowdays, the development of information and communication technology affect various aspects of life in society, one of the aspects is governance. Various innovations are designed to improve the effective service to the community. One of the services is a declaration of the concept of smart city. Denpasar is one of cities in Indonesia that has launched this concept by improving various services, either based on technology or not. Denpasar Smart City concept is described in six dimensions, such as smart economy, smart society, smart government, smart mobility, smart environment, and smart living pattern. These new services and innovations are important to be known by the public in Denpasar City. Communication by the government is the key, so that all these services can be understood and utilized by the community and other stakeholders. Public Relations as a communicator in the organization has a role to make it happen. In practice, government public relations in Indonesia has not been fully able to perform the role of public relations. This is due to the constraints on organizational structure, human resources, and facilities. This study examines how the role of Public Relations of Denpasar City Government in realizing Denpasar Smart City. This study used a qualitative approach with data collection conducted through interview method. According to this research, the fact is Public Relations Denpasar City in realizing Denpasar Smart City perform a big role in terms of publication. In addition, in the organization of Denpasar City Government, public relations has their role as facilitator and communication technician.   Keywords: DenpasarSmart City , Government Public Relation, The Role of Public Relation,